Peripartum cardiomyopathy in a 28-year-old patient—case report - Hajduk, Katarzyna; Gil, Aleksandra; Papis, Wojciech; Skórska, Gabriela; Śliwka, Joanna; Pawlak, Szymon; Hrapkowicz, Tomasz (Frontiers in Cardiovascular Medicine, 2025)
Peripartum cardiomyopathy (PPCM) is a rare but serious form of heart failure that occurs toward the end of pregnancy or in the earlypostpartum period. We present the case of a 28-year-old woman who developed severe biventricular heart failure and cardiac arrest shortly after childbirth. Despite treatment with mechanical circulatory support with veno-arterial extracorporeal membrane oxygenation (VA-ECMO) and intra-aorticballoon pump (IABP), her condition did not improve, and she was urgently referred for heart transplantation. Histological examination of theexplanted heart revealed noncompaction cardiomyopathy (NCC), a rare structural heart disease that may mimic PPCM. This case highlights the challenges in diagnosing PPCM and the importance of early intervention, including advanced support and transplant, in cases with poor recovery prospects.